2002
DOI: 10.1128/jvi.76.5.2469-2479.2002
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus BALF1 Is a BCL-2-Like Antagonist of the Herpesvirus Antiapoptotic BCL-2 Proteins

Abstract: Cellular BCL-2 family proteins can inhibit or induce programmed cell death in part by counteracting the activity of other BCL-2 family members. All sequenced gammaherpesviruses encode a BCL-2 homologue that potently inhibits apoptosis and apparently escapes some of the regulatory mechanisms that govern the functions of their cellular counterparts. Examples of these protective proteins include BHRF1 of Epstein-Barr virus (EBV) and KSBcl-2 of Kaposi's sarcoma-associated herpesvirus, also known as human herpesvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 77 publications
2
81
1
1
Order By: Relevance
“…64,65 Although they confirmed the interaction of BHRF1 with BOK by coprecipitation of in vitro translated proteins, we and others have failed to detect dimerization of BHRF1 with BAX, BAK, BAD (BH3-only protein) and Bcl-rambo by co-precipitation of transfected cell lysates or in GST pull-downs. 28,40,66,67 However, in these same experiments, the viral BCL-2 proteins from HVS and gHV68 were found to bind BAX. 28,40 Therefore, no consistent theme prevails, possibly suggesting that viral BCL-2 proteins may specifically target only one or possibly a subset of cellular pro-death factors to inhibit cell death.…”
Section: Viral and Cellular Bcl-2 Family Heterodimerization (Or Lack Of)mentioning
confidence: 97%
See 3 more Smart Citations
“…64,65 Although they confirmed the interaction of BHRF1 with BOK by coprecipitation of in vitro translated proteins, we and others have failed to detect dimerization of BHRF1 with BAX, BAK, BAD (BH3-only protein) and Bcl-rambo by co-precipitation of transfected cell lysates or in GST pull-downs. 28,40,66,67 However, in these same experiments, the viral BCL-2 proteins from HVS and gHV68 were found to bind BAX. 28,40 Therefore, no consistent theme prevails, possibly suggesting that viral BCL-2 proteins may specifically target only one or possibly a subset of cellular pro-death factors to inhibit cell death.…”
Section: Viral and Cellular Bcl-2 Family Heterodimerization (Or Lack Of)mentioning
confidence: 97%
“…28,40,66,67 However, in these same experiments, the viral BCL-2 proteins from HVS and gHV68 were found to bind BAX. 28,40 Therefore, no consistent theme prevails, possibly suggesting that viral BCL-2 proteins may specifically target only one or possibly a subset of cellular pro-death factors to inhibit cell death. However, we favour the idea that viral BCL-2 proteins may protect cells by alternate mechanisms.…”
Section: Viral and Cellular Bcl-2 Family Heterodimerization (Or Lack Of)mentioning
confidence: 97%
See 2 more Smart Citations
“…Similar results were found with anti-Fas plus interferon-γ (IFN-γ) when both cycloheximide and TNF-α or chloromethyl X-rosamine (CMXRos) staining were used to induce apoptosis (Marshall et al, 1999). However, a report showed that EBV BALF1 fails to protect cells from Bax-induced apoptosis in the DG75 B cell (EBV-negative BL lymphoma) (Bellows et al, 2002), so BALF1 lacks an anti-apoptotic function. Taken together, although the function of BALF1 is not yet clear, it remains possible that BALF1 interrupts the apoptotic pathway in EBV-infected cells by interacting with pro-apoptotic proteins, such as Bax and BAK.…”
Section: Balf1 Associates With Bax and Bakmentioning
confidence: 99%